2015
DOI: 10.4244/eijy15m01_03
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of second-generation everolimus-eluting stents versus first-generation sirolimus-eluting stents in acute myocardial infarction: three-year results of the XAMI trial

Abstract: The event rate at three years in this all-comer, randomised, multicentre AMI trial was low, including stent thrombosis, with no significant difference between first- and second-generation DES. Registration of trial:http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=1123 Candidate number: 2869; NTR number: NTR1123.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…The benefit of DESs, however, is limited to short‐term outcomes because of extremely late stent thrombosis in DESs, especially in first‐generation DESs in populations with CKD or high bleeding risk . In addition, no significant difference in long‐term outcomes among first‐generation DESs, second‐generation DESs, and BMSs was found. Moreover, these studies included small population sizes and presented conflicting findings.…”
Section: Introductionmentioning
confidence: 98%
“…The benefit of DESs, however, is limited to short‐term outcomes because of extremely late stent thrombosis in DESs, especially in first‐generation DESs in populations with CKD or high bleeding risk . In addition, no significant difference in long‐term outcomes among first‐generation DESs, second‐generation DESs, and BMSs was found. Moreover, these studies included small population sizes and presented conflicting findings.…”
Section: Introductionmentioning
confidence: 98%
“…Although SESs and PESs are not available at present, the present study would be useful for anticipating the outcomes of patients continuously treated at outpatients with first-generation DESs. In addition, since Hofma et al [19], reported that the event rate at 3 years was not significantly different between first (SES)-and second (everolimus-eluting stent; EES)-generation DES for acute myocardial infarction. Therefore, we could also participate the outcomes of the currently available EES as similar as the SES, the former (no-longer used) DES.…”
Section: Discussionmentioning
confidence: 97%
“…AMI is a serious coronary heart condition and AMI-associated ventricular remodeling is an important factor reducing the quality of life and survival rate of affected patients (15). The broad concept of AMI-associated ventricular remodeling implies that AMI is impacted by haemodynamics and non-haemodynamics, resulting in changes in heart size, shape and ultrastructure as well as damage of heart function (16).…”
Section: Discussionmentioning
confidence: 99%